Difference in the Prognostic Significance of N-Terminal Pro-B-Type Natriuretic Peptide between Cardioembolic and Noncardioembolic Ischemic Strokes. (5th March 2015) - Lee, Seung-Jae; Lee, Dong-Geun; Lim, Dal-Soo; Hong, Sukkeun; Park, Jin-Sik
Abstract : Background and Aim . Because B-type natriuretic peptide is a powerful predictor of heart failure, its capability to predict a fatal outcome in stroke might be limited to the cardioembolic stroke subtype. In this study, we attempt to ascertain the difference in the prognostic value of N-terminal pro-B-type natriuretic peptide (NT-proBNP) between cardioembolic and noncardioembolic stroke subgroups. Methods . 410 acute stroke patients were included. According to the presence of a cardioembolic source (CES), there were 221 patients with CES and 189 patients without CES. Logistic regression analysis was performed to ascertain the association between NT-proBNP and 6-month mortality/functional outcome in each group. Results . The mean age of our patients was 67.2 years (range, 18–97 years). NT-proBNP was a multivariate independent predictor of mortality in the CES group alone, whereas it was only a univariate predictor of 6-month mortality in the total patient and non-CES groups with its association disappearing in the multivariate model. In addition, it was only a univariate predictor of good functional outcome in all of the groups. Conclusions . Our data suggest that NT-proBNP can more reliably predict 6-month mortality in patients with cardioembolic stroke than in patients with other stroke subtypes.